A Design Study of an Off-axis Paraboloid Shaping Method for Central Receiver System Heliostats. (May 2015) - Meng, L.; You, Z.; Dubowsky, S.; Li, B.; Xing, F.
Abstract: The aberration of the heliostat shapes in the central receiver system can cause energy losses and limit their concentration abilities. Ideally the heliostat shapes should be off-axis paraboloids that adapt as a function of time and locations in the field.However, such heliostats are costly to realize. This paper proposed a heliostat design using a new shaping method that can approximately implement the adaptive off-axis paraboloids at a low cost. In this design, a simple offset-force loading mechanism bends a flat compliant mirror with two-dimensional tailored stiffness to form the sagittal and tangential curvatures simultaneously. It can be easily implemented by conventional manufacturing process and adjusted to location-based optimized shapes during assembly on site. A modular central receiver heliostat field in high-concentration application was modelled numerically. The results show substantial advantages of the location-only optimized design over the flat mirrors and uniform-stiffness mirrors. Anexperimental heliostat prototype was built to validate the concept. The mirror shapes were tested by coordinate measuring machines and outdoor solar concentrating experiments. The experiment results show that high performance could be achieved by the proposed design approach.